El grillo, el osos y el nino en el bano = A bug, a bear and a boy and the bath - McPhail, David, 1940- (New York : Scholastic Inc., 2001)
Three friends learn, love, and play together.
Bilingual.
Bilingual - each language has a cover and 8 pages bound upside down to each other
Keywords: Children's Stories, Bilingual; Friendship -- Juvenile fiction; Bears -- Juvenile fiction; Insects -- Juvenile fiction; Spanish language